The Case for Culturally Responsive Teaching in Pharmacy Curricula - Rockich-Winston, Nicole (Am J Pharm Educ, 2019)
Cultural diversity training in pharmacy education has evolved from standalone lectures to longitudinal courses, service-learning initiatives, rotation experiences and global health opportunities. Cultural competency frameworks have served as the scaffold for cultural diversity training, yet educators in other health care disciplines have called into question the utility of such frameworks and offered cultural humility as an alternative to foster development and lifelong learning. In order to implement and assess outcomes tied to cultural diversity successfully, this commentary discusses the five elements of culturally responsive teaching that will provide the tools necessary to integrate cultural humility across pharmacy curricula. In addition, we address how to approach faculty development to avoid common maladaptations in pedagogical movements and conclude with addressing the salient objectives to evaluate gains in student, institutional, and societal outcomes.